Comparison of Treatment Outcomes for Fluoroscopic and Fluoroscopy-free Endourological Procedures: A Systematic Review on Behalf of the European Association of Urology Urolithiasis Guidelines Panel - Davis, Niall F; Tzelves, Lazaros; Geraghty, Robert; Lombardo, Riccardo; Yuan, Cathy; Petrik, Ales; Neisius, Andrea; Gambaro, Giovanni; Jung, Helene; Shepherd, Robert; Tailly, Thomas; Somani, Bhaskar; et al. (European urology focus, 2023)
CONTEXT: Endourological procedures frequently require fluoroscopic guidance, which results in harmful radiation exposure to patients and staff. One clinician-controlled method for decreasing exposure to ionising radiation in patients with urolithiasis is to avoid the use of intraoperative fluoroscopy during stone intervention procedures. OBJECTIVE: To comparatively assess the benefits and risks of "fluoroscopy-free" and fluoroscopic endourological interventions in patients with urolithiasis. EVIDENCE ACQUISITION: A systematic review of the literature from 1970 to 2022 was performed using the MEDLINE/PubMed, Embase, and Cochrane controlled trials databases and ClinicalTrials.gov. Primary outcomes assessed were complications and the stone-free rate (SFR). Studies reporting data on ureteroscopy and percutaneous nephrolithotomy (PCNL) were eligible for inclusion. Secondary outcomes were operative duration, hospital length of stay, conversion from a fluoroscopy-free to a fluoroscopic procedure, and requirement for an auxiliary procedure to achieve stone clearance. EVIDENCE SYNTHESIS: In total, 24 studies (12 randomised and 12 observational) out of 834 abstracts screened were eligible for analysis. There were 4564 patients with urolithiasis in total, of whom 2309 underwent a fluoroscopy-free procedure and 2255 underwent a comparative fluoroscopic procedure for treatment of urolithiasis. Pooled analysis of all procedures revealed no significant difference between the groups in SFR (p = 0.84), operative duration (p = 0.11), or length of stay (p = 0.13). Complication rates were significantly higher in the fluoroscopy group (p = 0.009). The incidence of conversion from a fluoroscopy-free to a fluoroscopic procedure was 2.84%. Similar results were noted in subanalyses for ureteroscopy (n = 2647) and PCNL (n = 1917). When only randomised studies were analysed (n = 12), the overall complication rate was significantly in the fluoroscopy group (p < 0.001). CONCLUSIONS: For carefully selected patients with urolithiasis, fluoroscopy-free and fluoroscopic endourological procedures have comparable stone-free and complication rates when performed by experienced urologists. In addition, the conversion rate from a fluoroscopy-free to a fluoroscopic endourological procedure is low at 2.84%. These findings are important for clinicians and patients, as the detrimental health effects of ionising radiation are negated with fluoroscopy-free procedures. PATIENT SUMMARY: We compared treatments for kidney stones with and without the use of radiation. We found that kidney stone procedures without the use of radiation can be safely performed by experienced urologists in patients with normal kidney anatomy. These findings are important, as they indicate that the harmful effects of radiation can be avoided during kidney stone surgery.
Keywords: Urology; urologie; výsledek terapie; lidé; Urolithiasis; ledvinové kameny; Fluoroscopy; Treatment Outcome; Kidney Calculi; urolitiáza; Humans; fluoroskopie